Financial distress as a moderating variable of the influence of audit opinion and public accounting firm size on voluntary auditor switching - Choirul Huda; Ratno Agriyanto; Herwening Sindu Lestari; Bill Pangayow (Universitas Islam Negeri (UIN) Walisongo Semarang, 2021)
Purpose - This study aims to examine the effect of financial distress as a moderator of the effect of audit opinion and public accounting firm (KAP) size on auditor switching in companies listed on the Jakarta Islamic Index (JII) for the 2014-2019 period.Method - This study uses a sample of companies listed on the Jakarta Islamic Index (JII) for the 2014-2019 period. The number of companies sampled in this study were 12 companies. In this study, the researchers used a quantitative type of model and used the Statistical Package for Social Science (SPSS) version 16 for analyzing the data.Result - The results show that audit opinion and public accounting firm size have no effect on auditor switching, financial distress is not able to moderate the effect of audit opinion with auditor switching, and financial distress is not able to moderate the relationship between public accounting firm size and auditor switching.Implication - For stakeholders in motivating management to retain or replace auditors from various factors that are considered including audit opinion, public accounting firm size and financial distress.Originality - The object used in this study is a list of companies registered on JII. There is a 2-year additional period from the previous study, which was 4 years to 6 years. The measuring instrument for the financial distress variable used in this study is the Altman Z-score.